Feasibility study of disk diffusion susceptibility tests with Mueller-Hinton broth solidified with Gelrite, an agar substitute. - Barry, A L (1985)
Feasibility studies were done to determine whether a new agar substitute, Gelrite gellan gum, could be used to prepare a solid Mueller-Hinton medium for disk diffusion susceptibility tests. Mueller-Hinton broth was combined with 0.43% of the gellan gum and 0.75% KCI. The resulting medium had performance characteristics similar to those of Mueller-Hinton agars; however, zones on the gellan gum media tended to be a little larger. Significant differences among Mueller-Hinton broths and among Mueller-Hinton agars from different manufacturers were documented: zones on different lots of the gellan gum were more consistent. The Mueller-Hinton broth-gellan gum medium appears to represent a satisfactory alternative to agar media. However, because somewhat larger zones were seen on the gellan gum plates, further study will be needed to develop quality control limits and interpretive zone size standards for tests on this new medium.